2021
DOI: 10.2147/rmhp.s306402
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Perceived Risks Towards COVID-19 Pandemic and the Impact of Risk Communication Messages on Healthcare Workers in Saudi Arabia

Abstract: Purpose: To investigate knowledge, attitude, and perceived risks towards COVID-19 pandemic among healthcare workers (HCWs) in Saudi Arabia. Besides, the impact of risk communication strategy on the attitude and practice of HCWs was investigated. Patients and Methods: We conducted a cross-sectional study that targeted HCWs from various Saudi health facilities. We utilized a self-administrated, online-based questionnaire designed to assess basic knowledge of COVID-19, attitude and disease perception, and the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 48 publications
1
15
1
Order By: Relevance
“…24,31,32,37,[40][41][42][43][44][45]47,48,60,78,84,131 Mushi et al suggested that "risk communication as an effective strategy to improve the attitude and practice of HCWs towards COVID-19 in Saudi Arabia". 89 Measures to enhance protection for HCPs and minimize psychological consequences/potential social stigmatization should be recognized in the planning stage before any pandemic. 49,54,102 Also, it is essential that healthcare facilities provide more emotional/psychological support for all HCWs.…”
Section: Participants Online Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…24,31,32,37,[40][41][42][43][44][45]47,48,60,78,84,131 Mushi et al suggested that "risk communication as an effective strategy to improve the attitude and practice of HCWs towards COVID-19 in Saudi Arabia". 89 Measures to enhance protection for HCPs and minimize psychological consequences/potential social stigmatization should be recognized in the planning stage before any pandemic. 49,54,102 Also, it is essential that healthcare facilities provide more emotional/psychological support for all HCWs.…”
Section: Participants Online Questionnairementioning
confidence: 99%
“… 1300 participants Online questionnaire The Saudi MOH’s usage of social media platforms positively affected public health awareness concerning the reliability of natural remedies used during the pandemic. Mushi/Jul 2021 89 Knowledge, Attitude, and Perceived Risks Towards COVID-19 Pandemic and the Impact of Risk Communication Messages on Healthcare Workers in Saudi Arabia. 1691 responses Online questionnaire HCWs have fair knowledge/attitude towards the COVID-19 pandemic.…”
Section: The Searched Outcomesmentioning
confidence: 99%
“…Spreading risk awareness through different effective communication channels is a key driver in empowering the general population with the knowledge needed to do their part in alleviating the spread of COVID-19. During the pandemic, it is essential that any communicated information is clear, accurate, authoritative, reliable, easy to understand, accessible, leaves little to interpretation, and quickly shuts down any misinformation that can be potentially spread within the community [64] , [65] . The Saudi Ministry of Health (MoH) has been active in disseminating information to the general public to raise awareness of COVID-19 regarding general knowledge, risk factors, and preventive measures before and during the pandemic.…”
Section: Ksa Response To Covid-19 Pandemic: Mitigation Strategies By Using the Combined Modelmentioning
confidence: 99%
“…18 Risk communication has a direct two-way positive effect on risk protection behavior, and risk perception plays an intermediary role between risk communication and risk protection behavior. 14,19 Studies have shown that the level of individual risk perception will be affected by many factors such as psychology, society, culture, system, and individual attributes. The influencing factors of risk perception are diverse.…”
Section: Literature Reviewmentioning
confidence: 99%
“… 18 Risk communication has a direct two-way positive effect on risk protection behavior, and risk perception plays an intermediary role between risk communication and risk protection behavior. 14 , 19 …”
Section: Literature Reviewmentioning
confidence: 99%